The relationship between cash conversion cycle and firm profitability: evidence from consumer product firms in Malaysia / Nur Atikah Bakti - Bakti, Nur Atikah (2017)
The purpose of this study is to examine the relationship between cash conversion cycle and profitability on 50 consumer product firms listed in Bursa Malaysia for a period of five years from 2011 to 2015. The data collected from Thomson Reuteurs Data Stream and firms’ annual statement. The variables for this study were categorized into three part: dependent variable (Return On Equity and Return On Assets), independent variable (Cash Conversion Cycle and its component namely days inventory outstanding, days payable outstanding and days sales outstanding) and control variables (Size of Firm and Leverage). This study found a positive significant between cash conversion cycle and return on assets, and positive insignificant relationship between cash conversion and return on equity.